Thorax CT Scan Examination Procedure In Lung Tumor Cases At Bhayangkara Hospital Makassar - Rezki Amalia; Ni Putu Rita Jeniyanthi; I Made Adhi Mahendrayana (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2025)
Background: A CT scan is a media imaging tool that uses x-rays to obtain images/photos inside the body. Thorax CT Scan is performed to identify existing conditions in the mediastinum of the lungs. Therefore, the use of Slice Thickness is very influential in looking at the image quality of a Thorax CT Scan. Methods: This research uses qualitative research with a case study research design to investigate phenomena that occur in real life contexts using various sources as evidence. Results: The result of this research is that the use of a Slice Thickness of 3 mm in viewing image quality is good enough to display the structure of the anatomical image so that it can diagnose existing pathology. Conclusions: The Thorax CT Scan examination procedure in lung tumor cases at Bhayangkara Makassar Hospital has followed the applicable SOP. The results of the image quality using a Slice Thickness of 3 mm are quite good in diagnosing the patient's disease.